Synthesis of amino-sugars using the directed dihydroxylation reaction - Donohoe, T; Blades, K; Helliwell, M (1999)
The synthesis of protected forms of two amino-sugars, talosamine 1 and allosamine 2, is described; the syn, syn stereochemistry at C-2, C-3 and C-4 was controlled by the use of a hydrogen-bonding directed dihydroxylation reaction using stoichiometric and catalytic OsO4; proof of the relative stereochemistry of the allosamine series was obtained through an X-ray crystal structure of a protected derivative.